Портовый потенциал Украины - Кухарчик, В.Г. (Економічні інновації, 2011)
У статті розглядаються питання розвитку портового потенціалу України. Надана стратегія розвитку портового потенціалу Одеської області. Визначені напрямки розвитку портового комплексу України. The port's potential of Ukraineis examined. The development strategy of port potencial of Odessa region is presented. The directions of development of the port complex of Ukraine are deermined.